تأثير المؤامرة و الأزمة في الاقتصاد السوري وخاصة قطاع التجارة الخارجية - سلمان حيان أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2013)
يتضمن البحث رؤية تحليلية لتأثير المؤامرة والحصار والعقوبات الاقتصادية التي انعكست تداعياتها السلبية على كلّ الجوانب السياسية والاجتماعية والعسكرية والاقتصادية, وفي هذا البحث سنركزّ على الجانب الاقتصادي وبشكل خاص معدل النمو الاقتصادي وسعر الصرف والتجارة الخارجية أي الصادرات والمستوردات للفترة من عام 2006 ولغاية 2012, أي سنوات الخطة الخمسية العاشرة (2006– 2010) والسنتين الأولتين من الخطة الخمسية الحادية عشرة التي لم تقر بسبب المؤامرة والأزمة أي عامي (2011- 2012), وانطلقنا من ذلك لنتمكن من تحديد الآثار الاقتصادية للمؤامرة على المجتمع السوري, ولنؤكدّ أنّ الصراع هو على سورية وليس في سورية, إضافة إلى أن المؤامرة سترتب الكثير من الأعباء على المجتمع السوري, لأننا بحاجة كبيرة إلى المزيد من النفقات والوقت لإعادة إعمار ماخربته هذه المؤامرة التي يقودها الكيان الصهيوني والتحالف الغربي الأطلسي والرجعية العربية والأردوغانية العثمانية المتآمرة وغيرها من الدول المتضامنة معها بشكل مباشر أو غير مباشر, وفي دراستنا هذه اعتمدنا على اللغة التحليلية الرقمية, مع وضعنا لتصورات يمكن عدها خطوة في رسم معالم الخروج من هذه المؤامرة التي دخلت عامها الثالث منذ 15/3/2013, وخاصة أننا بدأنا نتلمس معالم نهايتها, والفضل الأول للشعب العربي السوري وقواتنا المسلحة والقيادة السورية وأصدقائنا, وأن سورية مستمرة في استكمال برنامجها الإصلاحي الذي بدأته منذ عام 2000 الذي تجسد بشكل واضح في خطاب القسم للسيد الرئيس الدكتور بشار الأسد بتاريخ 17/7/2000. The research involves analytical point of view of the impact of the great conspiracy that generated the crisis on Syria and its repercussions on all aspects of social, political, military, economic and other aspects of community life. In this research, we will focus on the economic side, especially the economic growth rate, the exchange rate and foreign trade imports and exports for a period from 2006 to 2012, which the tenth five-year plan (2006-2010) and the first two years of the eleventh five-year plan, which has not been decided because of the conspiracy and crisis in (2011-2012). We based on this to be able to determine the economic effects of the conspiracy on Syrian society, and reaffirm that the conflict is on Syria, not in Syria, adding to that the conspiracy would have a lot of burden on the Syrian society, because we need more expenses and time to rebuild the destruction caused by this conspiracy led by the Zionist entity, the Western Atlantic Alliance and Arabic and Ottoman-ardoghanet backwardness and other allies directly or indirectly. In this study we relied on the digital analytical language, putting in mind prospects that could be considered a step in charting out the plot to get out of this conspiracy, which entered its third year since 15/3/2013, especially we feel the aspects of its end, due to the efforts of the Syrian people, our armed forces, the Syrian leadership and our friends. Syria continues to complete its reform program initiated since 2000, embodied in the speech of President-Doctor Bashar Al-Assad on 17/7/2000, and we hope that we have taken all aspects of research in line with scientific research.